Drylot Backgrounding and Finishing Beef - Jones, Rodney D. (My University, 1999)
This publication helps a producer that buys calves and then backgrounds and finishes them, and uses projected input and output prices for illustrative purposes to find the break-even price.
MF593_1999_10
Keywords: MF593; Economics; Livestock; MF